1980
DOI: 10.1007/bf00428018
|View full text |Cite
|
Sign up to set email alerts
|

Treponema bryantii sp. nov., a rumen spirochete that interacts with cellulolytic bacteria

Abstract: A saccharolytic spirochete that associated and interacted with cellulolytic bacteria was isolated from bovine rumen fluid. Isolation was accomplished by means of a procedure involving serial dilution of a sample of rumen fluid into a cellulose-containing agar medium. Clear zones appeared within the medium as a result of cellulose hydrolysis by rumen bacteria. The saccharolytic spirochete and a cellulolytic bacterium later identified as a strain of Bacteroides succinogenes were isolated from the clear zones. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
135
0
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(145 citation statements)
references
References 20 publications
8
135
0
2
Order By: Relevance
“…The saccharolytic spirochete T. bryantii has been shown to be associated with the fibrolytic bacteria of the rumen and, albeit not possessing any fibrolytic activity, could enhance fiber degradation in a coculture with fibrolytic bacteria (16,30). In our experiment, the quantification of this bacterial DNA demonstrated kinetics similar to those of two fibrolytic bacteria, F. succinogenes and R. flavefaciens.…”
Section: Discussionsupporting
confidence: 51%
“…The saccharolytic spirochete T. bryantii has been shown to be associated with the fibrolytic bacteria of the rumen and, albeit not possessing any fibrolytic activity, could enhance fiber degradation in a coculture with fibrolytic bacteria (16,30). In our experiment, the quantification of this bacterial DNA demonstrated kinetics similar to those of two fibrolytic bacteria, F. succinogenes and R. flavefaciens.…”
Section: Discussionsupporting
confidence: 51%
“…The degradation of plant polysaccharides also accelerated cellulose and hemicellulose degradation [69]. In addition, in vitro studies have shown a beneficial interaction of Treponema bryantii with the cellulolytic bacterium Fibrobacter succinogenes [70]. The five main fibrolytic bacteria and plant polysaccharide degradation bacteria examined here represented 3.47% of the total genera reads.…”
Section: Core Prokaryotic Communities In the Rumenmentioning
confidence: 64%
“…In accordance with our proposal to designate a new genus for T. hyodysenteriae and T. innocens, the names Serpula hyodysenteriae and Serpula innocens are used in Table 1 and below. The conditions used for culturing and maintaining bacteria and additional strain characteristics have been described elsewhere (6,23,24,35,46,47). Cells were harvested during the exponential phase of growth.…”
Section: Methodsmentioning
confidence: 99%